Implications of Application Programming Interfaces for Third‐Party New App Development and Copycatting - Xue, Ling; Song, Peijian; Rai, Arun; Zhang, Cheng; Zhao, Xia (Production and operations management, 2019)
Digital platforms can use application programming interfaces (APIs) to support third‐party development of new apps and achieve growth at an unprecedented scale. However, there is also a dilemma between original new development and copycatting by third‐party suppliers. Motivated by this tension, we examined how APIs provided by digital platforms may influence two types of third‐party new app development: original apps and app copycatting. We also investigated how these influences are dependent on app market conditions. We empirically tested our theoretical conjectures using data on a leading web browser platform, and applying analytics techniques on app source code to identify original apps and copycat apps. Based on a difference‐in‐differences identification strategy, our findings suggest that the provision of platform APIs enhance the original new development of apps. While platform APIs may facilitate app copycatting as well, our findings suggest that platform APIs can enhance app suppliers’ relative attractiveness to original new development in comparison to copycatting. The enhancing effect of platform APIs on original new development is strengthened by app market potential and high market‐level app complexity. The enhancing effect of platform APIs on app copycatting is strengthened by app market potential and high market concentration. Our study has important theoretical and practical implications.